Step
*
1
2
2
1
2
2
1
of Lemma
int-to-ring-add
.....antecedent..... 
1. r : Rng
2. a1 : ℤ
3. a2 : ℤ
4. ∀x:ℤ. (int-to-ring(r;x + 1) = (int-to-ring(r;x) +r 1) ∈ |r|)
5. ∀x:ℤ. (int-to-ring(r;x - 1) = (int-to-ring(r;x) +r (-r 1)) ∈ |r|)
6. n : ℤ
7. 0 < n
8. ∀x:ℤ. (|x| < n - 1 
⇒ (∀y:ℤ. (int-to-ring(r;x + y) = (int-to-ring(r;x) +r int-to-ring(r;y)) ∈ |r|)))
9. x : ℤ
10. |x| < n
11. y : ℤ
12. ¬x < 0
13. ¬(x = 0 ∈ ℤ)
⊢ |x - 1| < n - 1
BY
{ xxx(MoveToConcl (-4) THEN (RWO  "absval_unfold" 0 THENA Auto) THEN RepeatFor 2 (AutoSplit) THEN Auto')xxx }
Latex:
Latex:
.....antecedent..... 
1.  r  :  Rng
2.  a1  :  \mBbbZ{}
3.  a2  :  \mBbbZ{}
4.  \mforall{}x:\mBbbZ{}.  (int-to-ring(r;x  +  1)  =  (int-to-ring(r;x)  +r  1))
5.  \mforall{}x:\mBbbZ{}.  (int-to-ring(r;x  -  1)  =  (int-to-ring(r;x)  +r  (-r  1)))
6.  n  :  \mBbbZ{}
7.  0  <  n
8.  \mforall{}x:\mBbbZ{}.  (|x|  <  n  -  1  {}\mRightarrow{}  (\mforall{}y:\mBbbZ{}.  (int-to-ring(r;x  +  y)  =  (int-to-ring(r;x)  +r  int-to-ring(r;y)))))
9.  x  :  \mBbbZ{}
10.  |x|  <  n
11.  y  :  \mBbbZ{}
12.  \mneg{}x  <  0
13.  \mneg{}(x  =  0)
\mvdash{}  |x  -  1|  <  n  -  1
By
Latex:
xxx(MoveToConcl  (-4)
        THEN  (RWO    "absval\_unfold"  0  THENA  Auto)
        THEN  RepeatFor  2  (AutoSplit)
        THEN  Auto')xxx
Home
Index